The effectivity of Trichoderma sp and Gliocladium sp. to control the Pokahbung disease (Fusarium moniliforme) on sugarcane (Saccharum officinarum) - puti ristha; Hasanuddin Hasanuddin; fatimah zahara (Universitas Sumatera Utara, 2018)
Pokahbung was one of some problems in Sugarcane cultivation. This experiment was aimed to test antagonist agent (Trichoderma sp and Gliocladium sp. ) to control Fusarium moniliforme. This study was conducted at screen house,at Agriculture Faculty, Universitas Sumatera Utara, Medan from March to October 2016th. It was done by using Completely Randomized Design (CRD) factorial with two factors and three replications. First factor was using antagonist agent (Trichoderma sp, Gliocladium sp., and combination of Trichoderma sp. and Gliocladium sp.) and the second factor was the concentration of antagonist agent 106 , 105, 104. The result showed: the best treatment was combination of Trichoderma sp. and Gliocladium sp. and with concentration 105and 106. Keywords: sugarcane, Fusarium moniliforme, Trichoderma sp., Gliocladium sp..